The Quality of Life of Women with Cervical Cancer in Indonesia: A Cross-Sectional Study - Afiyanti, Yati; Wardani, Ice Yulia; Martha, Evi (Nurse Media Journal of Nursing, 2019)
Background: Cervical cancer have significant impacts on the quality of life (QOL) of the women experiencing it. Limited studies are exploring QOL among Indonesian women diagnosed with cervical cancer.Purpose: This study aimed to investigate the QOL of women with cervical cancer who received radiation therapy and chemotherapy. Methods: A cross-sectional study was conducted to evaluate the QOL among 164 women with cervical cancer undergoing treatment. A consecutive sampling technique was used to recruit the samples. The EORTC QLQ-C 30 and QLQ-CX 24 were used to measure the QOL and sexual-related symptoms. The data collected were analyzed and presented as descriptive statistics in the form of means and standard deviations.  Results: The mean of the global health status of general well-being and QOL of the women was 54.56 ± 25.47. In the QOL subgroups of functional status, the physical function (55.94) and role functions (55.34) were most frequently reported to affect QOL. Regarding sexual-related symptoms of the women, sexual worry (52.72) and menopause symptoms (48.03) were the two most prevalent symptoms which impacted QOL.Conclusions: The quality of life of women with cervical cancer in Indonesia was generally at the higher end of the scale, and yet the majority of the women reported high prevalent symptoms of cancer and adverse effects of treatments. Comprehensive, high quality and culturally sensitive care for women with cervical cancer needs to be implemented in Indonesia, which has unique social and cultural beliefs.